Processo de monitoração de novas tecnologias em saúde - Pellizzoni, Leonardo (2019)
Systems embody domain knowledge originating from stakeholders which is implemented as business rules and specifies how the system works. Business rules exist independent of procedures, workflows and technologies, and also tend to remain more stable than the technologies used to carry out the operations performed by users in many user interfaces. A model to reuse the business rules with a high level of decoupling is proposed and applied in a layered software architecture. The findings support systems evolution and adaptations of continuously evolving technologies or new interfaces available to interact with users.